2010
DOI: 10.1021/jf904121y
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Effect on Shikimate, Nitrate Reductase Activity, Yield, and Seed Composition in Corn

Abstract: When glyphosate is applied to glyphosate-resistant (GR) crops, drift to nonglyphosate-resistant (non-GR) crops may cause significant injury and reduce yields. Tools are needed to quantify injury and predict crop losses. In this study, glyphosate drift was simulated by direct application at 12.5% of the recommended label rate to non-GR corn (Zea mays L.) at 3 or 6 weeks after planting (WAP) during two field seasons in the Mississippi delta region of the southeastern USA. Visual plant injury, shikimate accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 30 publications
5
30
1
7
Order By: Relevance
“…Corn kernels from each pot were analyzed for protein, oil, starch and fiber percentage using a near infrared (NIR) reflectance diode array feed analyzer (Petren, Springfield, IL) [20] [21]. Calibration equations were developed by Perten using Thermo Galactic Grams PLS IQ.…”
Section: Seed Composition Analysismentioning
confidence: 99%
“…Corn kernels from each pot were analyzed for protein, oil, starch and fiber percentage using a near infrared (NIR) reflectance diode array feed analyzer (Petren, Springfield, IL) [20] [21]. Calibration equations were developed by Perten using Thermo Galactic Grams PLS IQ.…”
Section: Seed Composition Analysismentioning
confidence: 99%
“…Nitrate stimulates nitrate reductase activity, whereas ammonium and nitrogen compounds accumulated in plants' tissues may repress nitrate assimilation. Reddy et al (2010) examined the influence of glyphosate simulated drift effect on non-glyphosate-resistant corn. They indicated that glyphosate drift significantly reduced both leaf nitrogen and nitrate reductase activity.…”
Section: Discussionmentioning
confidence: 99%
“…ha -1 (Vieira Jr. et al, 2015) and when evaluating production components, nitrogen content, protein and oil in the grains, and shikimate levels in the plant, at doses up to 1296 g a.i. ha -1 (Reddy et al, 2010). Some studies reported that glyphosate can cause problems for development for RR2 corn.…”
Section: Experiments Performed In Palotina -Pr (2015)mentioning
confidence: 99%